EFFECT OF KECEMCEM TREE (SPONDIAS PINNATA) BARK EXTRACT GEL TO INCREASE COLLAGEN POST WISTAR RATS CURETTAGE - Eka Pramudita Ramadhany; Media Sukmalia Adibah; Astrid Rahayu Dewi (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Periodontal treatment such as curettage and requires adjuvant therapy for healing process. One of the adjuvant therapies used is hyaluronic acid. Recently, several scientific studies have focused on the antioxidant and anti-inflammatory properties of various natural products such as kecemcem tree bark (Spondias pinnata) having a protective effect against oxidative and inflammatory changes that occur during the development of mucositis. This study aims to determine the effect of 70% Spondias pinnata bark extract gel to increase collagen fiber density after curettage on wistar rats. Material and Methods: Wistar rats were divided into 3 groups, negative control (CMC-Na gel), positive control (hyaluronic acid gel), and treatment group (70% Spondias pinnata bark extract gel). Mice were sacrificed and then histological preparations were made for further observation in three fields of view using a 400x magnification light microscope. Results and Discussions:  The average collagen density scoring value was higher than the positive control group and the negative control group. The results of the Mann-Whitney U test showed that there was a significant difference (p<0.05). Flavonoids, phenols, and β-sitosterol in kecemcem bark extract (Spondias pinnata) have an effect on increasing the density of collagen fibers after curettage as indicated by the higher average scoring value in the treatment group. Conclusion: It can be concluded that 70% 0% Spondias pinnata bark extract gel has the effect of increasing the density of gingival collagen fibers after curettage in Wistar rats (Rattus norvegicus).